(untitled) (Journal of Foreign Language Studies, 2024)
This research examined the perceptions of students and teachers towards the integration of multimedia visual aids (MVAs) in the English language classroom. It was based on Stake (1995) and Yin (2003)’s theoretical frameworks of case study research. A mixed-methods sequential explanatory design was used with the participation of 40 grade six students and 20 English teachers at a middle school in Hanoi, Vietnam. The study results showed discrepancies between the students’ and teachers’ perceived frequency of using MVAs in English lessons. However, both the teachers and students acknowledged the effects of these facilities in boosting their concentration, participation, and English language acquisition. The teachers also valued the effectiveness of MVAs in their preparation for lessons, time management, confidence, and teaching enthusiasm. However, some teachers, mostly older ones, voiced their reservations about the overuse of MVAs in lessons. The study results suggested that MVAs should be used more frequently but adequately, and teachers Should be provided with sufficient related training to reap the most significant benefit of the teaching-learning process.